The Contribution of Modern Chinese African Studies to the Promotion of National Interests in the African Direction - FITUNI Olga Leonidovna (Ученые записки Института Африки Российской академии наук)
The article examines the development of African studies in modern China and the interrelationship between the attitude of the Chinese state to the development of national African studies, on the one hand, and the promotion of the national interests of the People’s Republic of China in the African direction, on the other. The paper explores the stages of the formation of Chinese African studies, the existing institutional foundations for the development of African studies in the country, the connection between the rapid quantitative growth and qualitative rise of African studies in China during the last decade and a half with the success of regular China–Africa Forums. The author exposes the scope of research topics of Chinese Africanists. A separate part of the article is devoted to the analysis of Chinese studies on relations between Russia and African states. It displays the assessments on the part of Chinese scholars of the Sochi (2019) Summit and the Russia–Africa Business Forum as well as the influence of the Russian Federation on the continent.